DAMPAK KEBIJAKAN KREDIT, RESIKO ASET, DAN LEVERAGE TERHADAP KINERJA BANK - ariyani indriastuti; Theresia Susetyarsi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
The occurrence of the Covid-19 pandemic affected various sectors including banking due to the declining performance and ability to pay credit in the production sector to banks. The purpose of this study was to analyze the effect of the variable lending as measured by LDR, the effect of bank asset risk as measured by RWA, and bank leverage on bank performance. This study was conducted at 23 Commercial Banks in Indonesia, the results found that LDR and RWA had a significant positive effect on profitability. Leverage has a negative and insignificant effect on profitability Keywords: LDR, RWA, leverage, profitability